Factors Influencing Society’s Decision to Donate Waqf in the Bogor Waqf Forest: A Qualitative Study - Faza, Firdan Thoriq (Musyarakah: Journal of Sharia Economic (MJSE), 2025)
Introduction/Main Objectives: Muslims have varying tendencies when it comes to donating their wealth. Generally, Indonesians donate to mosques, schools, and cemeteries. However, over the past ten years, there has been an increasing trend of donating to nature conservation. This phenomenon raises several questions because it falls outside the "common" use of waqf. This study aims to investigate the motives for funding and how waqifs are involved in supporting Bogor Waqf Forests. Research Methods: A qualitative research design was applied as the data analysis method with the aim of gaining in-depth insight into the rationale behind the motives for waqf behavior. Respondents were selected using purposive sampling techniques. Specific criteria were established based on the research objectives: Muslim men and women who had donated a waqf of at least Rp 200,000 to the Bogor Waqf Forest. After selecting respondents who met the criteria, open-ended interviews were conducted. The quality of the information provided was the primary objective, ensuring that it could address the research questions. Triangulation techniques were applied to validate the data. Finding/Results: Basically, the decision of all respondents to donate their assets to the forestry sector is a form of implementation of a certain motivation. The results explain that the motives to donate waqf in Bogor Waqf Forest are driven by spiritual values, ecological wisdom, empowerment space, and nazhir credibility. Conclusion: Waqif motives serve as a basis for fundraising for waqf in the forestry sector. Nazhir can use the motive data to maximize the role of waqif to make a more significant contribution to the development of the Bogor Waqf Forest